Dyskurs performatywny w literaturoznawstwie - Krajewska, Anna (Przestrzenie Teorii, 2008)
The author discusses the reasons for the absence of the so-called performative turn in Poland and argues that the apparent lack of a theory of drama in literary studies has denied a possibility to have the changes going on within discourses of the discipline perceived properly. By making advantage of the notion of dramatic quality to determine literary epistemology (dramatic cognition) one can facilitate the process of redefining categories in literary studies. The author demonstrates the current shift in artistic practice from text-oriented thinking to that of a performative system effecting the reshaping of the discourse of literary studies and proposes accordingly a dramatic theory (of literature, aesthetics, anthropology and culture) that results in performance studies become one of the essential research methods in modern literary studies.